Hospital Information System for Motivating Patient Loyalty: A Systematic Literature Review - Alismaili S.N.R.; Shanmugam M.; Kasim H.A.; Magalingam P. (Springer Science and Business Media Deutschland GmbH, 2023)
Digital libraries; Health care; Hospitals; Information systems; Information use; Motivation; Conference papers; Empirical studies; Healthcare services; Hospital information systems; Patient loyalties; Patient satisfaction; Systematic literature review; Systematic Review; Medical computing